2018
DOI: 10.1037/cou0000260
|View full text |Cite
|
Sign up to set email alerts
|

Promoting forgiveness: Characteristics of the treatment, the clients, and their interaction.

Abstract: Forgiveness-based group treatments to address interpersonal hurts have been shown to be efficacious across a range of therapy models (Wade, Hoyt, Kidwell, & Worthington, 2014). However, little is known about how treatment and individual characteristics may interact in predicting outcomes. The present study examined a sample of 162 community adults randomly assigned to three treatment conditions; an 8-week REACH Forgiveness intervention (Worthington, 2006), an 8-week process group, and a waitlist control. Hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 41 publications
(63 reference statements)
2
34
0
1
Order By: Relevance
“…Those in the REACH Forgiveness intervention reported greater improvements, compared to controls, in forgiveness, as well as, relationship quality, empathy, and negative mood across 1-, 3-, 6-, and 12-month follow-up assessments (Worthington et al, 2015). Again, similar to the present findings, a recent RCT with 162 middle-aged adults comparing a 12hour, in-person, REACH Forgiveness group condition to a 12-hour, in-person, process group therapy condition and a wait-list control showed that the REACH Forgiveness group condition was better than the wait-list condition at reducing unforgiveness and rumination and increasing empathy and benevolence at mid-, and post-intervention and 6-month followup assessments, but REACH Forgiveness was equally effective as process group therapy focused on forgiveness on these same outcomes (Wade et al, 2018). Furthermore, several other studies have evaluated the REACH Forgiveness program using 6 to 13 h in-person trainings, downloadable workbooks, and online materials.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Those in the REACH Forgiveness intervention reported greater improvements, compared to controls, in forgiveness, as well as, relationship quality, empathy, and negative mood across 1-, 3-, 6-, and 12-month follow-up assessments (Worthington et al, 2015). Again, similar to the present findings, a recent RCT with 162 middle-aged adults comparing a 12hour, in-person, REACH Forgiveness group condition to a 12-hour, in-person, process group therapy condition and a wait-list control showed that the REACH Forgiveness group condition was better than the wait-list condition at reducing unforgiveness and rumination and increasing empathy and benevolence at mid-, and post-intervention and 6-month followup assessments, but REACH Forgiveness was equally effective as process group therapy focused on forgiveness on these same outcomes (Wade et al, 2018). Furthermore, several other studies have evaluated the REACH Forgiveness program using 6 to 13 h in-person trainings, downloadable workbooks, and online materials.…”
Section: Discussionmentioning
confidence: 92%
“…It showed benefits only for empathy (Nation et al, 2018). Thus it is important to determine whether REACH Forgiveness methods are capable of generating not only benefits to forgiveness and unforgiveness, but also other closely related outcomes (e.g., involving emotional expressivity and mood and also self-esteem) that have been shown to be positively affected in United States samples (Sandage and Worthington, 2010;Sandage et al, 2015;Worthington et al, 2015;Wade et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a RCT of 145 newly married couples, individuals in nine-hour, in-person, REACH Forgiveness program delivered in couple counseling reported greater improvements, compared to controls, in forgiveness, as well as relationship quality, empathy, negative mood, coded behavior, and salivary cortisol across 1-, 3-, 6-, and 12-month follow-up assessments (Worthington et al, 2015). Recently, a RCT with 162 middle-aged adults comparing a 12-hour, in-person, REACH Forgiveness group condition to a 12-hour, in-person, Yalom-based process group therapy condition and a wait-list control showed that the REACH Forgiveness psychoeducational group condition was better than the wait-list condition at reducing unforgiveness and rumination and increasing empathy and benevolence at pre-, mid-, and post-intervention and six-month follow-up assessments, but REACH Forgiveness was no more effective than the process group therapy for these same outcomes (Wade et al, 2018).…”
Section: Reach Forgiveness Efficacy Studiesmentioning
confidence: 99%
“…Almost all intervention studies have compared one treatment to either an assessment-only, waiting list, or alternative treatment that is not necessarily aimed primarily at promoting forgiveness (like relaxation training). Two noted exceptions exist (Hart & Shapiro, 2002; Wade et al, 2018). This is a third.…”
Section: Present Studymentioning
confidence: 99%
“…Although Njus and Okerstrom (2016) found among their sample that romantic avoidance was only negatively and weakly predictive of in-group loyalty, friendship avoidance and God-attachment avoidance were both negatively and weakly associated with individuating morals. Additionally, avoidant attachment style has also been found to be predictive of less forgiveness (e.g., Davis et al, 2008; Wade et al, 2018).…”
Section: Moral Foundations Theory and Unforgivenessmentioning
confidence: 99%